Effects of psychology teachers’ didactic performance on student didactic performance - Capa-Luque, Walter; Bazán-Ramírez, Aldo; Mayorga-Falcón, Luz Elizabeth; Barboza-Navarro, Evelyn; Hervias-Guerra, Edmundo; Montgomery-Urday, William; Bello-Vidal, Catalina; García-Ramírez, Danna Rocio (Frontiers in Psychology, 2025)
There is an abundance of literature on students’ evaluations of their teachers’ didactic performance. However, few studies have investigated the relationship between teachers’ didactic performance and its effect on students’ didactic performance, with self-reports that have a solid basis in the substantive theory of such measurements. This study presents a cross-sectional and predictive analysis of the effects of teacher didactic performance (TDP) on student didactic performance (DPPS), examined through structural models that incorporate primary, second-order, and mediating factors within a causal framework. A total of 757 psychology students from a Peruvian public university (171 males and 586 females), selected by non-probabilistic sampling, participated in the study. The scales assessing student perception of teaching didactic performance and self-assessment of their didactic performance were administered. The structural regression model analyzing the direct and indirect effects of the six TDP criteria on the six DPPS criteria presented satisfactory fit indices: χ2(1048) = 2569.701, CFI = 0.928, TLI = 0.923, RMSEA = 0.044, SRMR = 0.064. This model demonstrates that the indirect effects of teaching performance, mediated by SDP criteria such as pre-current learning, illustration-participation, relevant practice, and feedback-enhancement, have a joint impact of 77% on the student criterion evaluation-application (transfer of disciplinary competencies). The second structural model analyzing the direct and indirect effects of the two second-order factors (teaching and formative assessment) of the TDP on the six criteria of the DPPS also presented adequate fit indices: χ2(1061) = 2564.619, CFI = 0.929, TLI = 0.924, RMSEA = 0.043, SRMR = 0.058. Together, the two second-order factors presented indirect effects with an overall impact of 69% on the criterion evaluation-application. Finally, the third model, which incorporates two chain mediators, analyzes the effects of the two second-order quantitative factors of the TDP on the two second-order quantitative factors of the DPPS. This model highlights that the highest ranking indirect effect between teaching and student criterion improvement-application occurs when formative assessment serves as a mediator. It is concluded that the possibility for students to improve, apply, and transfer their professional competencies to the solution of disciplinary problems depends on the optimization of formative assessment, which is linked to the teaching factor that corresponds to the teacher’s didactic performance.